The coevolution of central banks and the concept of monetary policy - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2023)
The explicit concepts of a central bank and monetary policy were not fully articulated until the 20th century, although, with some degree of circumspection, they can be used retrospectively in regard to earlier times. The oldest central banks were hardly central banks in the modern sense at their foundings. Rather they coevolved with the financial system and money itself. This paper traces that coevolution and the related coevolution of monetary policy from commodity money and policies related to the maintenance of the quality of the coin or intentional debasement to support the fiscal aims of the state, through the support of the banking system in crises, to the fiat money of today and policies of macroeconomic control.
Keywords: 330